Anticoccidial effect of Fructus Meliae toosendan extract against Eimeria tenella - Ting Yong; Meng Chen; Yunhe Li; Xu Song; Yongyuan Huang; Yaqin Chen; Renyong Jia; Yuanfeng Zou; Lixia Li; Lizi Yin; Changliang He; Cheng Lv; et al. (Taylor & Francis Group, 2020)
Context Fructus Meliae toosendan extracts (FMTE) have a good therapeutic effect on coccidiosis, but there is no relevant research on its prophylactic effect on coccidiosis. Objective This study comprehensively evaluates the anticoccidial effect of FMTE. Materials and methods In vitro, the unsporulated oocysts were treated with serial dilutions of FMTE and incubated for 7 d, and the sporulated oocysts were counted for calculating the median lethal concentration (LC50) of FMTE. In vivo, 180 10-day-old broiler chickens free of coccidiosis were weighted and randomly distributed into six groups: normal group, untreated group, 4 protective groups (positive group and three FMTE groups). From day 10 to day 21, chickens in the three FMTE groups were pre-treated with FMTE at the dosage of 2.5, 5 and 10 g/kg/d, respectively, and chickens in the positive group were pre-treated with qiuliling (10 g/kg/d). On day 14, chickens in all groups except the normal group were orally infected with 1.5 × 104 sporulated oocysts. The clinical symptoms were observed from day 10 to day 21, the anticoccidial index (ACI), tissue lesions, and intestinal microflora were determined on day 21. Results FMTE showed anti-sporulation effect against E. tenella and the LC50 value was 245.83 µg/mL in vitro. In vivo, FMTE at the dosage of 10 g/kg/d was effective against E. tenella infection, and its ACI value was 162.56, which was higher than the value of positive drug qiuliling (128.81). Discussion and conclusions: FMTE have potent anticoccidial effects, and it presents an alternative anticoccidial agent for avian coccidiosis control.